2019
DOI: 10.1053/j.gastro.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Model to Calculate Harms and Benefits of Early vs Delayed Liver Transplantation for Patients With Alcohol-Associated Hepatitis

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e17 (https://www. gastrojournal.org/cme/home). Learning Objective: Upon completion of this CME activity, successful learners will be able to state the expected short-and long-term outcomes of a patient with severe, medically refractory, acute alcohol-associated hepatitis presented with 2 different transplant eligibility policies: early (ie, without minimum period of sobriety) versus delayed (eg, 6-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
3
35
0
2
Order By: Relevance
“…Due to the fact that a randomised controlled trial may be a questionable study design for demonstrating the benefits of early liver transplantation in patients with severe AH, Lee et al have performed a modelling approach that tests immediate transplantation versus a delayed procedure. 41 In this study, early transplantation was associated with improved survival, despite the negative impact of alcohol relapse on outcomes. However, this strategy needs to be confirmed in prospective studies.…”
Section: N-acetylcysteinementioning
confidence: 63%
“…Due to the fact that a randomised controlled trial may be a questionable study design for demonstrating the benefits of early liver transplantation in patients with severe AH, Lee et al have performed a modelling approach that tests immediate transplantation versus a delayed procedure. 41 In this study, early transplantation was associated with improved survival, despite the negative impact of alcohol relapse on outcomes. However, this strategy needs to be confirmed in prospective studies.…”
Section: N-acetylcysteinementioning
confidence: 63%
“…Lee et al found early liver transplantation provided a survival benefit for candidates with severe AAH, regardless of risk of posttransplant alcohol use, but the survival benefit of liver transplantation was reduced with post-transplant alcohol use. 16 These studies in the United States and Europe provide evidence supporting the role of early liver transplantation for severe AAH and for reevaluation of the 6-month rule.…”
Section: Early Liver Transplantation In the United Statesmentioning
confidence: 83%
“…6 months of abstinence) liver transplantation among patients with severe AAH and varying degrees of alcohol use posttransplant. 16 This study quantified the survival benefit of early liver transplantation and the number of life-years lost after liver transplant due to resumed alcohol use. Lee et al found early liver transplantation provided a survival benefit for candidates with severe AAH, regardless of risk of posttransplant alcohol use, but the survival benefit of liver transplantation was reduced with post-transplant alcohol use.…”
Section: Early Liver Transplantation In the United Statesmentioning
confidence: 99%
“…A central issue is identifying when LT is justified in patients with AH. A recent study reported a notable survival benefit with early LT for AH in comparison to late LT. 10 Such data are of utmost importance and may continue to shift the attitude toward early LT for AH patients. In our analysis, we noticed that the median time from registration on the OPTN waiting list to receiving an LT decreased dramatically from 58 days in the 2004–2009 period to 5 days in the 2014–2018 period (Table S3, SDC, http://links.lww.com/TXD/A286 ).…”
Section: Discussionmentioning
confidence: 99%